2006
DOI: 10.1111/j.1399-3089.2006.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood groups and transfusions in pigs

Abstract: The blood groups of pigs are important to transplantation research because some are also important transplantation antigens and because pigs undergoing organ or hematopoietic transplantation may require transfusion support. There is considerable literature on the subject but much of it is not in transplant related journals. We will review this literature and also give some practical advice on transfusion support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 66 publications
2
71
2
Order By: Relevance
“…In piglets, abundant expression of blood group antigens in kidney was reported by Rydberg et al (15) and is confirmed by our results. However, in contrast to earlier reports of A antigen expression in pig endothelium and endocardium (17), we did not detect A antigen in porcine cardiac tissue or vascular endothelium, consistent with later studies (13). This may be attributed to differences in techniques and antibodies used.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In piglets, abundant expression of blood group antigens in kidney was reported by Rydberg et al (15) and is confirmed by our results. However, in contrast to earlier reports of A antigen expression in pig endothelium and endocardium (17), we did not detect A antigen in porcine cardiac tissue or vascular endothelium, consistent with later studies (13). This may be attributed to differences in techniques and antibodies used.…”
Section: Discussioncontrasting
confidence: 82%
“…Pigs have been reported to have a blood group AO system comparable with the human ABO system (13), with genetically defined specific glycosyltransferases controlling A and H antigen expression in various tissues (14,15). Similar to humans, pigs produce ''natural'' antibodies against nonself ABH antigens, that is, group A pigs produce anti-B antibodies and group O pigs produce both anti-A and anti-B antibodies (16).…”
mentioning
confidence: 98%
“…Anti-blood group A and B mAbs did not react with the GalT-KO and WT fractions (not shown). Pigs are known to be of either blood group O or A (30) and the lack of anti-A staining indicates that this pig strain is of blood group O since small intestine epithelial cells of blood group A pigs contain large amounts of A glycolipid determinants (31).…”
Section: Neutral Glycolipid Compoundsmentioning
confidence: 98%
“…In many transplant studies using primates as recipients and pigs as donors, these antigens remain an unknown and untested variable. 35 According to our findings; there are several blood antigens on primates that could act as haemagglutinins. Even more, a severe mismatch between the blood antigens between donor and recipient could trigger rejection in xenotransplantation as has been previously demonstrated in kidney allotransplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The immune response to these transfused blood components may affect the outcome of these experiments and should be considered when designing transplant studies. 35 The use of microtyping cards in primates may have some limitations. Firstly, these cards include reagents derived from human sera, that may contain antispecies panagglutinins or anti-alpha-gal antibodies resulting in falsepositives, as it has been previously demonstrated. )…”
Section: Discussionmentioning
confidence: 99%